ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DALAM PEMBELAJARAN DARING BERBANTU POWER POINT DIMASA PANDEMI COVID-19 DI SMP NEGERI 1 BATANG ANGKOLA - Pilipus Kandase Sitompul; Rahmatika Elindra; Eva Yanti Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Abstrack This study aims to analyze mathematical problem solving skills in online learning assisted by power point during the covid-19 pandemic at SMK Negeri 1 Batang Angkola. This research approach is descriptive qualitative. The research subjects were 15 students. Observations, tests, and interviews were used in data collection and triangulation techniques were used in analytical techniques. The results showed that the average problem-solving ability in online learning assisted by power point was 70.42 (good category). It was concluded that mathematical problem solving skills in online learning assisted by power point at SMK Negeri 1 Batang Angkola included students understanding the problem, planning, solving problems according to plan and re-examining. Keywords: mathematical problem solving skills, online learning, assisted power point